(untitled) (Indian Journal of Chemistry (IJC), 2024)
Using natural feedstock extract we have successfully accomplished the Henry reaction at room temperature. Herein, we used a very simple and highly abundant waste material to prepare natural base such as ‘Water Extract of Leaf Ash of Neem’ (WELAN). It is remarkable that the catalytic system does not require activation or any toxic ligand, additive/promoter, base, organic solvent and so on. A range of substituted aldehydes were screened to investigate the scope of this protocol.